2021
DOI: 10.1007/s40889-021-00135-1
|View full text |Cite
|
Sign up to set email alerts
|

The teaching of computer ethics on computer science and related degree programmes. a European survey

Abstract: Within the Computer Science community, many ethical issues have emerged as significant and critical concerns. Computer ethics is an academic field in its own right and there are unique ethical issues associated with information technology. It encompasses a range of issues and concerns including privacy and agency around personal information, Artificial Intelligence and pervasive technology, the Internet of Things and surveillance applications. As computing technology impacts society at an ever growing pace, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Indeed, some ethical statements in these guidelines are meaningless without the proper ethical acculturation. For example, ethical education in computer science degrees in Europe is often a standalone subject with limited hours (Stavrakakis et al, 2022 ). The discourse often addresses stakeholders' responsibilities (using terms such as ‘should’ or ‘shall’).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some ethical statements in these guidelines are meaningless without the proper ethical acculturation. For example, ethical education in computer science degrees in Europe is often a standalone subject with limited hours (Stavrakakis et al, 2022 ). The discourse often addresses stakeholders' responsibilities (using terms such as ‘should’ or ‘shall’).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Europe in 2020 about the teaching of ethics in computer science or related programs, 36% of the respondents report that their institutions did not teach ethics. However, the ones that did teach them, they did so in AI and related areas (64%), and machine learning and related topics (51%) [20].…”
Section: What Do the Universities Teach?mentioning
confidence: 99%
“…In a study conducted in Europe in 2020 about the teaching of ethics in computer science or related programs, 36% of the respondents reported that their institutions did not teach ethics. However, the ones that did teach them did so in AI and related areas (64%) and machine learning and related topics (51%) [31].…”
Section: What Do the Universities Teach?mentioning
confidence: 99%